Effects of substrate temperature on the microstructure, surface morphology and optical properties of Cu-doped ZnO films. (November 2015) - Yu, Y.; Liu, Y.; Wang, Q.; Li, Y. L.; Wang, Z.
Abstract : Cu-doped ZnO films with a single phase (002) oriented hexagonal wurtzite structure were prepared on glass substrates by magnetron co-sputtering. The influences of substrate temperature on the microstructure, surface morphology and optical properties of the films were systematically investigated. We found that increasing temperature can enlarge the crystal grains and improve the crystallinity of the films. The change of deposition temperature can cause the shift of optical absorption line and influence the band gap. These optical effects of substrate temperature can be attributed to the different Cu content in the films.